A Comparative Approach for Environmental Justice Analysis: Explaining Divergent Societal Distributions of Particulate Matter and Ozone Pollution across U.S. Neighborhoods. Issue 2 (7th February 2022) - Collins, Timothy W.; Grineski, Sara E.; Nadybal, Shawna M.
Abstract : Numerous environmental justice (EJ) studies demonstrate that U.S. racial and ethnic minorities experience disparate hazard exposures, but we lack knowledge about how the societal distribution of risk varies between hazard types and how neighborhood-level racial residential segregation influences patterns of environmental injustice. We address those limitations by comparatively analyzing disparities in exposures to fine particulate matter (PM2.5 ) and ground-level ozone (O3 ) across census tracts of the contiguous United States and by elucidating the role of local racial residential segregation in structuring environmental injustices based on minority versus White neighborhood composition. Results indicate divergent societal patterns of exposure to the two pollutants. Tracts with higher PM2.5 have greater proportions of Hispanic, Black, and Asian and Pacific Islander residents, whereas tracts with increased O3 have lower proportions of those racialized groups. Additionally, we find that local multigroup racial residential segregation modifies the effect of minority versus White composition on PM2.5 exposures, such that residents of segregated minority neighborhoods breathe air laden with more PM2.5, whereas those in segregated White neighborhoods inhale air with less PM2.5 . We find the opposite pattern for O3 . Our comparative EJ perspective illuminates how the association between privileged Whiteness and O3 pollution is neither unjust nor equalizes the distribution of risk.